Comparision of Effects of Rosuvastatin Versus Atorvastatin Treatment on Plasma Levels of Asymmetric Dimethylarginine in Patients With Hyperlipidemia Having Coronary Artery Disease - ATAŞ, HALİL (SAGE PUBLICATIONS INC, 2014)
Elevated plasma levels of asymmetric dimethylarginine (ADMA) are prevalent in patients with hypercholesterolemia and coronary artery disease. A total of 83 patients with hypercholesterolemia and angiographically documented mild coronary artery stenosis were randomized to rosuvastatin treatment (20 mg) or atorvastatin treatment (40 mg) once daily for 6 weeks after a 4-week dietary lead-in phase. Both statins decreased total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglyceride levels effectively. Only rosuvastatin increased high-density lipoprotein cholesterol (HDL-C) levels. Both rosuvastatin and atorvastatin decreased plasma ADMA levels; rosuvastatin had a significantly greater effect. The reduction in ADMA levels were correlated with the reduction in TC and LDL-C levels as well as LDL-C-HDL-C ratio. Treatment with rosuvastatin or atorvastatin in patients with hyperlipidemia with mild coronary artery stenosis may lead to a decrease in ADMA levels, which may contribute to improved endothelial function.
Keywords: asymmetric dimethylarginine; hypercholesterolemia; coronary artery disease; rosuvastatin; atorvastatin; NITRIC-OXIDE SYNTHASE; STAGE RENAL-DISEASE; STATIN TREATMENT; ENDOTHELIAL DYSFUNCTION; L-ARGININE; RISK; ADMA; CHOLESTEROL; SIMVASTATIN; EFFICACY